Corticopallidal Connectome of the Globus Pallidus Externus in Humans: An Exploratory Study of Structural Connectivity Using Probabilistic Diffusion Tractography - Grewal, S.S.; Holanda, V.M.; Middlebrooks, E.H. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Electrophysiologic abnormalities of the globus pallidus externus have been shown in several disease processes including Parkinson disease, dystonia, and Huntington disease. However, the connectivity, nuclear structure, and function of the globus pallidus externus are still not well-understood. Increasing evidence for the existence of direct corticopallidal connections challenges traditional understanding of the connectivity of the globus pallidus externus; nevertheless, these corticopallidal connections have yet to be fully characterized in humans. The objective of this study was to assess the corticopallidal connections of the globus pallidus externus by means of probabilistic diffusion-weighted MR imaging tractography using high-resolution, multishell data.MATERIALS AND METHODS: Imaging data from the open-access Human Connectome Project data base were used to perform probabilistic tractography between the globus pallidus externus and the cerebral cortex using 34 distinct cortical regions. Group averages were calculated for normalized percentages of tracts reaching each of the cortical targets, and side-to-side comparison was made.RESULTS: Cortical connectivity was demonstrated between the globus pallidus externus and multiple cortical regions, including direct connection to putative sensorimotor, associative, and limbic areas. Connectivity patterns were not significantly different between the right and left hemispheres with the exception of the frontal pole, which showed a greater number of connections on the right (P = .004).CONCLUSIONS: Our in vivo study of the human globus pallidus externus using probabilistic tractography supports the existence of extensive corticopallidal connections and a tripartite functional division, as found in animal studies. A better understanding of the connectivity of the globus pallidus externus may help to understand its function and elucidate the effects of programming the higher contacts in pallidal deep brain stimulation.DBSdeep brain stimulationGPeglobus pallidus externus